'Home is Another Country': A Foucauldian Reading of Sisonke Msimang's Always Another Country. Issue 2 (3rd July 2022) - Henning, John
Abstract: Sisonke Msimang's Always Another Country is an intimate account of the lifelong search for 'home' by its autobiographical narrator, the child of exiled South African parents. My essay argues that Msimang's figuring of a complicated, nationally-organized external realm through the exilic subjectivity of its narrator provides an opportunity to read a series of spaces in the text as what Michel Foucault, in 'Of Other Spaces' (1986), calls 'utopias' and 'heterotopias'. Simply put, South Africa exists as a non-real space – a utopia – for most of the memoir. It carries down telephone wires and from television screens into the mind of Sonke, where it is reproduced as an alternate, imagined version of itself. On the other hand, 'real' spaces – living rooms, principals' offices, family homes – all develop characteristics of Foucauldian heterogeneity. They are sites within sites or, as Peter Johnson explains, microcosms of reverse social ordering. Rather than producing an overly theoretical rendering of a deeply personal text, my essay aims to show the benefits of Foucauldian approaches in conceptualizing and understanding the complicated ways in which exiled-subjects occupy space in our nationally-organized world.